Jurnal ILMU KOMUNIKASI: PUBLIC’S ATTRIBUTION VS PUNITIVE BEHAVIOR IN INDONESIAN PUBLIC RELATIONS PRACTICE - Rachmat Kriyantono, Yuyun Agus Riani, Rizky Ika Safitri (PRODI Ilmu Komunikasi UAJY, 2017)
The research aims to test situational crisis communication and attribution theories in Indonesian context. Crisis threats companies’ reputation and affects the public’s attribution which will lead to the creation of punitive behavior from the public towards the organization.